Organic-inorganic composite material, method for producing the same, and electrolyte
Patent Information
- Application Number
- CN202611031119.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-13
AI Technical Summary
这些界面副反应会导致电池容量快速衰减、内阻显著上升,并可能引发热失控等安全隐患
本申请提供的有机-无机复合材料通过设计的多臂星形分子具有较大的空间位阻提供了分子级的稳定性,无机粒子通过共价键与多臂星形分子紧密结合,形成协同保护机制。并且,本申请中的多臂星形分子结构中引入了温度响应性分子,可以适应高低温环境下的变化,不仅可以提供开放的离子通道,还能在高温下发生有序重排在正极/电解质界面形成更致密的界面保护层,在电解液中使用时,可以满足高能量密度锂电池在宽温度范围和快速充电条件下的应用需求。
Smart Images

Figure CN122907736A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to an organic-inorganic composite material, its preparation method, and an electrolyte. Background Technology
[0002] Under high-rate charging and high-temperature operating conditions, lithium-ion batteries are highly susceptible to continuous side reactions at the solid-liquid interface between the cathode material and the electrolyte, including electrolyte oxidation and decomposition, and unstable growth of the interfacial film. These interfacial side reactions can lead to rapid capacity decay, a significant increase in internal resistance, and may even trigger safety hazards such as thermal runaway.
[0003] In related technologies, common strategies for improving interface modification mainly include replacing the electrolyte with a polymer electrolyte or adding an inorganic coating to the electrode surface. These methods have alleviated the side reactions between the electrode and the electrolyte to some extent, but each has certain limiting factors. For example, it is difficult to simultaneously ensure the room temperature ionic conductivity and mechanical strength of polymer electrolytes; the addition of inorganic coatings increases the difficulty of ion conduction, and the uniformity of the coating is difficult to control.
[0004] Therefore, developing a solution to effectively mitigate side reactions in lithium-ion batteries under high-rate charging and high / low-temperature operating conditions has become a very important research topic. Summary of the Invention
[0005] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, this application provides an organic-inorganic composite material, its preparation method, and an electrolyte. The organic-inorganic composite material provided in this application serves as a stabilizing modifier for the cathode / electrolyte interface of a lithium-ion battery, effectively protecting the cathode / electrolyte interface and avoiding side reactions in lithium-ion batteries under high-rate charging and high-temperature operating conditions, while maintaining good ion conductivity, thus meeting the application requirements of high-energy-density lithium batteries under wide temperature ranges and fast charging conditions.
[0006] To achieve the above-mentioned objectives, this application provides the following technical solution: The first aspect of this application provides an organic-inorganic composite material obtained through a reaction of inorganic particles and temperature-responsive molecularly modified multi-arm star molecules; wherein... The temperature-responsive molecule-modified multi-armed star molecule is obtained by reacting at least one temperature-responsive molecule with at least one functionalized multi-armed star molecule; The functionalized multi-arm star molecule comprises at least one hydroxyl-terminated multi-arm prepolymer obtained by treatment with a functionalizing agent; The structure of the hydroxyl-terminated multiarm prepolymer is shown in Formula I: Formula I, Wherein, B is the non-hydroxyl portion of a compound containing at least four hydroxyl groups, and n is 4 to 8; Ar for R is a substituted or unsubstituted C4-C7 alkyl group.
[0007] As an optional implementation, the hydroxyl-terminated multiarm prepolymer satisfies at least one of the following conditions: (1) The number average molecular weight of the hydroxyl-terminated multiarm prepolymer is 15-50 kg / mol; (2) The arm length of the hydroxyl-terminated multi-arm prepolymer is 6.5~13 kg / mol; (3) The PDI of the hydroxyl-terminated multiarm prepolymer is 1.0~2.0.
[0008] As an optional implementation, the raw materials for preparing the hydroxyl-terminated multiarm prepolymer include the compound containing at least four hydroxyl groups and the lactone compound, and satisfy at least one of the following conditions: (1) The compound containing at least four hydroxyl groups includes polyols with a functionality of 4 to 8; (2) The compound containing at least four hydroxyl groups includes at least one of pentaerythritol, dipentaerythritol, inositol or sorbitol; (3) The lactone compound includes at least one of δ-valerolactone, ε-caprolactone, η-heptylactone or ξ-octylactone.
[0009] As an optional implementation, the functionalized reagent contains an olefinic unsaturated component that can polymerize with temperature-responsive molecules; And / or, the functionalizing agent includes at least one of 3-(isobutenoyloxy)propyltrimethoxysilane and vinyltrimethoxysilane.
[0010] As an optional embodiment, the temperature-responsive molecule comprises at least one temperature-responsive monomer and at least one unsaturated carboxylic acid, and satisfies at least one of the following conditions: (1) The temperature-responsive monomer includes at least one of N-isopropylacrylamide, N-vinylcaprolactam, N,N-dimethylaminoethyl methacrylate, N,N-diethylacrylamide, 2-hydroxyethyl acrylate, N-isopropylmaleimide or 2-isopropenyl-2-oxazoline; (2) The unsaturated carboxylic acid includes at least one of acrylic acid, methacrylic acid, itaconic acid, maleic acid or fumaric acid.
[0011] As an optional implementation, the inorganic particles satisfy at least one of the following conditions: (1) The inorganic particles include at least one of Al2O3, ZrO2, TiO2 or SiO2; (2) The inorganic particles are obtained by treatment with aminosilane; the aminosilane includes at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane or N-octadecyl-aminopropyltrimethoxysilane. (3) The particle size of the inorganic particles is 10nm~50nm.
[0012] The second aspect of this application provides a method for preparing an organic-inorganic composite material, comprising the following steps: S1: Treat the hydroxyl-terminated multi-arm prepolymer with the functionalizing agent to obtain a functionalized multi-arm star molecule; S2: The temperature-responsive molecule reacts with the functionalized multi-armed star molecule to obtain a temperature-responsive molecule-modified multi-armed star molecule; S3: React the temperature-responsive molecule-modified multi-armed star-shaped molecule with the inorganic particles to obtain the organic-inorganic composite material.
[0013] As an optional implementation, the weight ratio of the inorganic particles and the temperature-responsive molecule-modified multi-armed star molecules in S3 is 1:(1~5).
[0014] A third aspect of this application provides an electrolyte comprising an electrolyte salt, an organic solvent, and the organic-inorganic composite material described above, or an organic-inorganic composite material prepared by the preparation method described above.
[0015] As an optional implementation, the electrolyte satisfies at least one of the following conditions: (1) The amount of the organic-inorganic composite material added accounts for 1% to 4% of the total mass of the electrolyte; (2) The organic solvent includes at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate or ethyl acetate; (3) The electrolyte salt includes at least one of LiPF6, LiFSI, LiTFSI, LiBF4, LiClO4, and LiBOB; (4) The concentration of the electrolyte salt is 0.8-1.2 mol / L.
[0016] The organic-inorganic composite material, its preparation method, and the electrolyte provided in this application have the following beneficial effects: The organic-inorganic composite material provided in this application utilizes a multi-armed star molecule with significant steric hindrance to offer molecular-level stability. Inorganic particles are tightly bound to the multi-armed star molecule via covalent bonds, forming a synergistic protection mechanism. Furthermore, the multi-armed star molecule structure in this application incorporates temperature-responsive molecules, allowing it to adapt to changes in high and low temperature environments. It not only provides open ion channels but also undergoes ordered rearrangement at high temperatures to form a denser interfacial protective layer at the cathode / electrolyte interface. When used in the electrolyte, it can meet the application requirements of high-energy-density lithium batteries under wide temperature ranges and fast charging conditions.
[0017] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0018] Figure 1 The graph shows a comparison of the 25°C cycle test results of batteries assembled with electrolytes containing organic-inorganic composite materials prepared in Example 1 and Comparative Example 1. The baseline group 1# is Comparative Example 1, and the improvement group 2# is Example 1.
[0019] Figure 2 The graph shows a comparison of the DCR test results of batteries assembled with electrolytes containing organic-inorganic composite materials prepared in Example 1 and Comparative Example 1 at 25°C. The baseline group 1# is Comparative Example 1, and the improvement group 2# is Example 1.
[0020] Figure 3 The discharge curves of a battery (Improved Group 2#) assembled with an electrolyte containing the organic-inorganic composite material prepared in Example 1 at different rates are shown.
[0021] Figure 4 The discharge curves of a battery (baseline group 1#) assembled with an electrolyte containing the organic-inorganic composite material prepared in Comparative Example 1 at different rates are shown.
[0022] Figure 5 The graph shows a comparison of the storage capacity retention rate of batteries assembled with electrolytes containing organic-inorganic composite materials prepared in Example 1 and Comparative Example 1 at 60°C. The baseline group 1# is Comparative Example 1, and the improvement group 2# is Example 1.
[0023] Figure 6 The graph shows a comparison of the storage capacity recovery rate test results of batteries assembled with electrolytes containing organic-inorganic composite materials prepared in Example 1 and Comparative Example 1 at 60°C. The baseline group 1# is Comparative Example 1, and the improvement group 2# is Example 1. Detailed Implementation
[0024] To make the technical solution and beneficial effects of this application more apparent and understandable, a detailed description is provided below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional experimental conditions. Unless otherwise specified, all reagents and raw materials used in this application are commercially available.
[0025] In the following description, numerous specific details are set forth in order to provide a more thorough understanding of this application. However, it will be apparent to those skilled in the art that this application can be practiced without one or more of these details. In other instances, to avoid confusion with this application, some technical features well-known in the art have not been described; that is, not all features of actual embodiments are described herein, nor are well-known functions and steps described in detail.
[0026] In the description of this application, it should be noted that the terms "first," "second," etc., are used for descriptive purposes only and are not intended to indicate or imply relative importance.
[0027] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0028] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0029] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0030] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0031] [Organic-inorganic composite materials] In related technologies, the solution of improving electrolyte formulation and enhancing electrolyte performance by adding external additives such as inorganic nanoparticles often suffers from the problem that the added additives are difficult to disperse and it is difficult to take into account the improvement of electrolyte performance at different temperatures, thus affecting the battery's lifespan and high-rate performance.
[0032] In view of this, this application provides an organic-inorganic composite material obtained by reacting inorganic particles with multi-armed star molecules modified by temperature-responsive molecules.
[0033] The temperature-responsive molecule-modified multi-armed star molecule is obtained by reacting at least one temperature-responsive molecule with at least one functionalized multi-armed star molecule. The functionalized multi-arm star molecule comprises at least one hydroxyl-terminated multi-arm prepolymer obtained by treatment with a functionalizing agent; The structure of the hydroxyl-terminated multiarm prepolymer is shown in Formula I: Formula I, Wherein, B is the non-hydroxyl portion of a compound containing at least four hydroxyl groups, and n is 4 to 8; Ar for R is a substituted or unsubstituted C4-C7 alkyl group.
[0034] In this paper, the term "inorganic particles" refers to inorganic minerals or artificially synthesized granular materials that are insoluble in water.
[0035] In this paper, the term "temperature responsiveness" refers to the ability of a material or molecule to produce a perceptible, reversible change in its physical or chemical properties in response to changes in ambient temperature. This response typically manifests as changes in molecular chain conformation, solubility, volume phase transition, or surface charge, with the core characteristic being the existence of a critical transition temperature.
[0036] In this paper, the term "molecular modification" refers to the introduction of functional molecules or groups onto a molecular chain through chemical bonding to alter its original properties.
[0037] In this document, the term "multi-armed star molecule" refers to a branched macromolecular structure consisting of a central core and multiple linear arms radiating outward from the central core. The central core is a single atom, functional group, or small molecule backbone, and the arms are identical or different polymer segments or molecular chains. In this application, a preferred central core is a structure with at least four reactive sites to connect four or more functional arms.
[0038] In this paper, the term "temperature-responsive molecule" refers to a molecule that can respond to changes in ambient temperature and undergo reversible changes in physical or chemical properties near a critical temperature (including the lowest critical dissolution temperature LCST or the highest critical dissolution temperature UCST).
[0039] In this paper, the term "functionalization" refers to the introduction of specific functional groups into multi-arm star molecules to acquire chemical activities that they did not originally possess.
[0040] In this paper, the term "hydroxyl-terminated" refers to the chemical state in which the end of a molecular chain is terminated by a hydroxyl group.
[0041] In this paper, the term "the hydroxyl-free portion of a compound with at least four hydroxyl groups" refers to the skeletal structure remaining after removing all hydroxyl groups from a polyhydroxy compound molecule having four or more hydroxyl groups.
[0042] In this paper, the term "C4-C7 alkyl" refers to a straight-chain or branched hydrocarbon chain group consisting only of carbon and hydrogen atoms, without any unsaturation, having 4 to 7 carbon atoms, and attached to the rest of the molecule by single bonds.
[0043] In the organic-inorganic composite material provided in this application, the hydroxyl-terminated multi-arm prepolymer includes compounds containing at least four hydroxyl groups. The hydroxyl-free portion of these compounds is chemically bonded to the carbonyl carbon of the Ar structure to form a -C(O)-O- ester bond, resulting in a stable hydroxyl-terminated multi-arm prepolymer with B as the core and Ar structure as the arms. The multi-arm prepolymer in this application is chemically bonded and remains stable under polymerization conditions, avoiding the interfacial separation problem of traditional physical adsorption. Furthermore, the hydroxyl-terminated multi-arm prepolymer provided in this application has a uniform arm length distribution, laying the foundation for the uniform modification of subsequent temperature-responsive molecular chain segments. The temperature-responsive molecules introduced into the temperature-responsive multi-arm star-shaped molecule modified in this application can intelligently adjust their conformation according to temperature changes. At low temperatures, the molecules expand to expose inorganic particles, forming open transport channels; at high temperatures, the molecules contract to construct a dense interfacial protective layer, preventing side reactions in the battery electrode. The multi-channel ion transport network ensures efficient ion conduction at different temperatures, meeting the application requirements of high-energy-density lithium batteries under wide temperature ranges and fast charging conditions.
[0044] [Hydroxy-terminated multi-arm prepolymer] In some optional embodiments, the number-average molecular weight of the hydroxyl-terminated multi-arm prepolymer is 15-50 kg / mol; as an example, the number-average molecular weight of the hydroxyl-terminated multi-arm prepolymer can be 15 kg / mol, 18 kg / mol, 21 kg / mol, 27 kg / mol, 32 kg / mol, 34 kg / mol, 37 kg / mol, 38 kg / mol, 41 kg / mol, 42 kg / mol, 44 kg / mol, 46 kg / mol, 48 kg / mol, 50 kg / mol, etc., or any value within the above range. When the number-average molecular weight of the hydroxyl-terminated multi-arm prepolymer is below 15 kg / mol, the molecular chain is too short, resulting in insufficient steric hindrance effect, and inorganic particles are prone to agglomeration in the system; while when the number-average molecular weight of the hydroxyl-terminated multi-arm prepolymer exceeds 50 kg / mol, its use in electrolytes significantly increases electrolyte viscosity and reduces lithium-ion migration rate, limiting its application.
[0045] In some optional embodiments, the arm length of the hydroxyl-terminated multi-arm prepolymer is 6.5~13 kg / mol; as an example, the arm length of the hydroxyl-terminated multi-arm prepolymer can be 6.7 kg / mol, 8 kg / mol, 8.5 kg / mol, 9.5 kg / mol, 10 kg / mol, 10.3 kg / mol, 11 kg / mol, 11.5 kg / mol, 12 kg / mol, 12.5 kg / mol, 13 kg / mol, etc., or it can be any value within the above range, without specific limitation. When the arm length of the hydroxyl-terminated multi-arm prepolymer is less than 6.5 kg / mol, the molecular chains cannot form an effective protective layer, and the dispersion stability decreases significantly; when the arm length of the hydroxyl-terminated multi-arm prepolymer exceeds 13 kg / mol, molecular chain entanglement occurs, which limits the responsiveness of temperature-responsive molecules, resulting in the inability to expose inorganic particles in time at high temperatures.
[0046] In some optional embodiments, the PDI of the hydroxyl-terminated multi-arm prepolymer is 1.0 to 2.0; as an example, the PDI of the hydroxyl-terminated multi-arm prepolymer can be 1.17, 1.22, 1.27, 1.35, 1.43, 1.45, 1.55, 1.67, 1.85, 2.0, etc., or it can be any value within the above range, without specific limitation. Further optionally, the PDI of the hydroxyl-terminated multi-arm prepolymer is 1.17 to 1.55. The hydroxyl-terminated multi-arm prepolymer provided in this application has a uniform length and height of each arm, which helps to form a functional layer with uniform structure and stable performance during subsequent coupling with inorganic particles.
[0047] In this document, the term "number-average molecular weight of multi-arm prepolymers" refers to the average molecular weight of hydroxyl-terminated multi-arm prepolymers counted by molecular number. It should be noted that the number-average molecular weight of the hydroxyl-terminated multi-arm prepolymers in this application was determined by gel permeation chromatography (GPC), using polystyrene as a standard and tetrahydrofuran as the mobile phase.
[0048] In this document, the term "arm length of a multi-arm prepolymer" refers to the average number-average molecular weight (usually denoted as Marm or simply arm length) of each arm constituting the multi-arm prepolymer. It represents the average length of the linear segment from the core reactive site to the terminal hydroxyl group. It should be noted that the arm length of the multi-arm prepolymer in this application can be calculated based on the known number of arms and the number-average molecular weight of the multi-arm prepolymer, as shown in Equation II: Formula II Where Marm is the arm length of the multi-arm prepolymer in kg / mol, Mn is the number-average molecular weight of the multi-arm prepolymer in kg / mol, and f is the number of arms of the multi-arm prepolymer.
[0049] In this document, the term "PDI of multi-arm prepolymer" refers to the Polydispersity Index (PDI) of the multi-arm prepolymer. It should be noted that the PDI in this application is calculated using the weight-average molecular weight and number-average molecular weight obtained from GPC testing, as shown in Equation III: PDI= Formula III Wherein, Mw is the weight-average molecular weight of the multi-arm prepolymer, and Mn is the number-average molecular weight of the multi-arm prepolymer. Both are obtained simultaneously by gel permeation chromatography (GPC) in the same test.
[0050] In some alternative embodiments, the raw materials for preparing the hydroxyl-terminated multiarm prepolymer include the compound containing at least four hydroxyl groups and the lactone compound.
[0051] Further optionally, the compound containing at least four hydroxyl groups includes a polyol with a functionality of 4 to 8; as an example, the functionality of the compound containing at least four hydroxyl groups can be 4, 5, 6, 7, or 8. If the functionality is too high, the uniformity of the arm length of the resulting hydroxyl-terminated multi-arm prepolymer will be affected; if the functionality is too low, it will result in the inability to form an effective star-shaped molecule, leading to steric hindrance and poor thermal stability in the multi-arm prepolymer, making it unsuitable as an effective lithium-ion battery cathode / electrolyte interface stabilizer over a wide temperature range, and failing to solve the problem of side reactions occurring under high-temperature battery operating conditions.
[0052] Further optionally, the compound containing at least four hydroxyl groups includes at least one of pentaerythritol, dipentaerythritol, inositol, or sorbitol.
[0053] Further optionally, the lactone compound includes at least one selected from δ-valerolactone, ε-caprolactone, η-heptanolactone, or ξ-octanolactone. Even further, the lactone compound includes at least one selected from ε-caprolactone or η-heptanolactone.
[0054] In some alternative embodiments, the molar ratio of the compound containing at least four hydroxyl groups to the lactone compound is 1:(4~8); as an example, the molar ratio of the compound containing at least four hydroxyl groups to the lactone compound may be 1:4, 1:5, 1:6, 1:7, 1:8, etc.
[0055] Polyols with a functionality of 4-8 can undergo ring-opening polymerization with lactone compounds to form highly symmetrical star-shaped multi-arm structures. This structure can be applied in electrolytes, where it can form a stable three-dimensional network. The uniform arm length allows the molecular chains to expand at low temperatures, forming open ion transport channels, while at high temperatures, the molecules contract to build a dense interfacial protective layer, preventing electrolyte decomposition.
[0056] [Functionalized reagents] In some alternative embodiments, the functionalized reagent contains an olefinic unsaturated component that can polymerize with temperature-responsive molecules.
[0057] In this paper, the term "olefinic unsaturated component" refers to a compound, monomer, oligomer, or polymer fragment containing one or more carbon-carbon double bonds in its molecular structure.
[0058] Further optionally, the functionalizing agent includes at least one of 3-(isobutenoyloxy)propyltrimethoxysilane or vinyltrimethoxysilane; even further, the functionalizing agent may be 3-(isobutenoyloxy)propyltrimethoxysilane.
[0059] In this application, the hydroxyl-terminated multi-arm prepolymer is further modified by functionalizing reagents to introduce silicon-oxygen bonds and olefinic unsaturated components that can polymerize with temperature-responsive molecules into the molecular structure. The silicon-oxygen bond-reinforced structure and steric hindrance effect provide molecular-level stability, laying the foundation for the subsequent use of the organic-inorganic composite material prepared from it in electrolytes to improve the high and low temperature stability of electrolytes.
[0060] [Temperature-responsive molecules] In some alternative embodiments, the temperature-responsive molecule comprises at least one temperature-responsive monomer and at least one unsaturated carboxylic acid.
[0061] Further optionally, the temperature-responsive monomer includes at least one of N-isopropylacrylamide, N-vinylcaprolactam, N,N-dimethylaminoethyl methacrylate, N,N-diethylacrylamide, 2-hydroxyethyl acrylate, N-isopropylmaleimide, or 2-isopropenyl-2-oxazoline; even further, the temperature-responsive monomer may be N-isopropylacrylamide.
[0062] Further optionally, the unsaturated carboxylic acid includes at least one selected from acrylic acid, methacrylic acid, itaconic acid, maleic acid, and fumaric acid; even further, the unsaturated carboxylic acid may be acrylic acid.
[0063] [Inorganic particles] In some alternative embodiments, the inorganic particles include, but are not limited to, at least one of Al2O3, ZrO2, TiO2 or SiO2; furthermore, the inorganic particles may be Al2O3 or ZrO2.
[0064] In some alternative embodiments, the inorganic particles are obtained by treatment with an aminosilane; the aminosilane includes at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane or N-octadecyl-aminopropyltrimethoxysilane.
[0065] In some optional embodiments, the particle size of the inorganic particles is 10nm to 50nm; as an example, the particle size of the inorganic particles can be 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, or any combination of the above two values.
[0066] By controlling the particle size of inorganic particles within the aforementioned range, both dispersion stability and nano-effects are taken into account, enhancing the chemical bonding ability between inorganic particles and organic molecules, and enabling uniform coverage of organic-inorganic hybrid structures at the molecular level.
[0067] In related technologies, organic additives are prone to decomposition and failure at high temperatures due to poor thermal stability, while inorganic coatings suffer from increased interfacial impedance due to poor ionic conductivity. Therefore, this application innovatively develops an organic-inorganic composite material for electrolytes. This composite material comprises temperature-responsive multi-armed star molecules, achieving dynamic interfacial protection through temperature-dependent changes in molecular conformation. When the temperature is below the LCST, the side chains of the temperature-responsive molecules form strong hydrogen bonds with water molecules, and the molecular chains fully hydrate and extend, forming a hydrophilic network structure. At this time, the inorganic particles in the organic-inorganic composite material are exposed to the electrolyte, establishing open lithium-ion transport channels. When the temperature is above the LCST, the hydrogen bonds break, the molecular chains dehydrate, shrink, and aggregate, forming a dense organic protective layer that encapsulates the inorganic particles, effectively blocking side reactions between the electrolyte and the positive electrode. Furthermore, the synergistic effect of the multiple arms in the multi-armed star molecules significantly enhances the steric hindrance effect, keeping the inorganic particles highly dispersed in the electrolyte and avoiding uneven interfacial protection caused by agglomeration in traditional physical mixing. Organic-inorganic covalent bonding further ensures the chemical stability of the structure, enabling the temperature response function to remain highly efficient during long-term cycling, thereby simultaneously resolving the technical contradiction between high-temperature stability and low-temperature ion conductivity.
[0068] [Preparation methods for organic-inorganic composite materials] The second aspect of this application provides a method for preparing an organic-inorganic composite material, comprising the following steps: S1: Treat the hydroxyl-terminated multi-arm prepolymer with the functionalizing agent to obtain a functionalized multi-arm star molecule; S2: The temperature-responsive molecule reacts with the functionalized multi-armed star molecule to obtain a temperature-responsive molecule-modified multi-armed star molecule; S3: React the temperature-responsive molecule-modified multi-armed star-shaped molecule with the inorganic particles to obtain the organic-inorganic composite material.
[0069] It should be understood that all the features and advantages described above for "organic-inorganic composite materials" also apply to the "preparation method of organic-inorganic composite materials", and will not be repeated here.
[0070] [Preparation of Functionalized Multi-Arm Star Molecules] In some alternative embodiments, the preparation method of the functionalized multi-arm star molecule includes: S11: A compound containing at least four hydroxyl groups and a lactone compound are chemically reacted to obtain a hydroxyl-terminated multi-arm prepolymer; S12: Treat the hydroxyl-terminated multi-arm prepolymer with a functionalizing agent to obtain a functionalized multi-arm star molecule.
[0071] As an example, S11 can be a reaction of pentaerythritol and ε-caprolactone under a catalyst in a nitrogen atmosphere to obtain a hydroxyl-terminated multi-arm prepolymer.
[0072] It should be noted that this application does not limit the specific type of catalyst used in the preparation of hydroxyl-terminated multi-arm prepolymers, and the catalyst can be selected according to the actual situation, as long as it can achieve the technical solution of this application; and the reaction time and reaction temperature are not specifically limited, and conventional reaction conditions can be used, such as reacting at 110°C for 8 hours, or reacting at 105°C for 8.5 hours, or reacting at 120°C for 7.5 hours, etc.
[0073] [Preparation of temperature-responsive molecularly modified multi-arm star molecules] In some alternative embodiments, the method for preparing temperature-responsive molecularly modified multi-arm star molecules includes the following steps: The functionalized multi-armed star molecule prepared above, along with a temperature-responsive monomer and an unsaturated carboxylic acid, are reacted to obtain a temperature-responsive molecularly modified multi-armed star molecule.
[0074] As an example, the preparation method of temperature-responsive molecularly modified multi-armed star molecules can be as follows: the functionalized multi-armed star molecules prepared above, N-isopropylacrylamide, acrylic acid and an initiator are reacted in an organic solvent under nitrogen protection, purified by dialysis, and freeze-dried to obtain temperature-responsive molecularly modified multi-armed star molecules.
[0075] It should be noted that this application does not limit the specific type of initiator used in the preparation of temperature-responsive molecularly modified multi-arm star molecules. The initiator can be selected according to the actual situation, as long as it achieves the technical solution of this application. Examples include azo initiators, peroxide initiators, redox initiation systems, photoinitiators, and combinations thereof. For example, azobisisobutyronitrile (AIBN) can be used. This application also does not limit the reaction time and temperature in the preparation of temperature-responsive molecularly modified multi-arm star molecules. Conventional reaction conditions are sufficient, such as reacting at 60℃ for 12 hours, at 58℃ for 14 hours, or at 65℃ for 11 hours. This application also does not limit the specific type of organic solvent used in the preparation of temperature-responsive molecularly modified multi-arm star molecules. The solvent can be selected according to the actual situation, as long as it achieves the technical solution of this application.
[0076] The temperature-responsive polymer segments (PNIPAM) introduced into the multi-arm star molecule can intelligently adjust their conformation according to temperature changes. At low temperatures, the molecules expand to form open ion transport channels, while at high temperatures, they contract to build a dense interfacial protective layer. Simultaneously, the multi-channel ion transport network (including interstitial channels between nano-oxide particles and inter-molecular arms) ensures efficient ion conduction at different temperatures, enabling the battery to maintain excellent cycle life and rate performance even in extreme temperature environments. Through temperature-responsive molecular design and multi-scale interfacial modulation, stable application of the electrolyte within a wide temperature range of -20℃ to 60℃ has been achieved.
[0077] [Method for treating inorganic particles with aminosilane] In some alternative embodiments, the method of treating inorganic particles with aminosilane includes the following steps: Inorganic particles are treated with aminosilane to obtain silane-treated inorganic particles; Further optionally, the aminosilane includes at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane or N-octadecyl-aminopropyltrimethoxysilane; further optionally, the aminosilane may be 3-aminopropyltriethoxysilane.
[0078] Further optionally, the method for treating inorganic particles with aminosilane includes the following steps: Inorganic particles were dispersed in an organic solvent, and then 3-aminopropyltriethoxysilane was added. The mixture was reacted, centrifuged, and the silane-treated inorganic particles were obtained.
[0079] It should be noted that this application does not limit the specific type of organic solvent used in the aminosilane treatment process, and the solvent can be selected according to the actual situation, as long as it can achieve the technical solution of this application.
[0080] [Preparation of Organic-Inorganic Composite Materials] Organic-inorganic composite materials are obtained by chemical reaction of silane-treated inorganic particles and temperature-responsive molecularly modified multi-arm star molecules.
[0081] In some alternative embodiments, the chemical reaction conditions include condensation reactions of inorganic particles and temperature-responsive molecularly modified multi-armed star molecules in the presence of N,N'-dicyclohexylcarbodiimide and 4-dimethylaminopyridine under organic solvent conditions.
[0082] In some alternative embodiments, silane-treated inorganic particles are subjected to ultrasonic conditions with temperature-responsive molecularly modified multi-arm star molecules.
[0083] In some alternative embodiments, the frequency of the ultrasound is 20 to 40 kHz; for example, the ultrasound frequency can be 20 kHz, 25 kHz, 30 kHz, 40 kHz, etc.
[0084] In some optional embodiments, the weight ratio of the silane-treated inorganic particles to the temperature-responsive molecularly modified multi-armed star molecules is 1:(1~5); further optionally, the weight ratio of the silane-treated inorganic particles to the temperature-responsive molecularly modified multi-armed star molecules is 1:(1~3); as an example, the weight ratio of the silane-treated inorganic particles to the temperature-responsive molecularly modified multi-armed star molecules can be 1:1, 1:2, 1:3, etc.
[0085] When the weight ratio of silane-treated inorganic particles to temperature-responsive multi-armed star-shaped molecules is less than 1:1, the surface coverage is less than 70%, and the inorganic nanoparticles are locally exposed to the electrolyte, exacerbating electrolyte decomposition side reactions at high temperatures. When the ratio exceeds 1:5, excessive modifying molecules form multilayer adsorption on the particle surface, leading to entanglement between molecular chains and bridging of adjacent particles, causing inorganic particle aggregation. Ion transport channels are physically blocked, interfacial impedance increases, and the specific surface area of aggregated particles decreases, resulting in the loss of nano-effects and ultimately deteriorating cycle life.
[0086] By employing an organic-inorganic hybrid design, the problem of poor thermal stability of traditional organic additives is solved: nano-oxide particles (such as Al2O3, TiO2, and ZrO2) form a thermally stable framework due to their high melting point and physical barrier effect, while multi-armed star molecules provide molecular-level stability through the structure strengthened by silicon-oxygen bonds and the steric hindrance effect. The two are tightly bound together by covalent bonds to form a synergistic protection mechanism, which not only effectively blocks heat transfer and captures decomposition free radicals, but also allows for ordered rearrangement at high temperatures to form a denser interfacial protective layer, significantly improving the stability and protective effect of organic-inorganic composite materials in high-temperature environments.
[0087] Electrolyte A third aspect of this application provides an electrolyte comprising an electrolyte salt, an organic solvent, and the organic-inorganic composite material described above, or an organic-inorganic composite material prepared by the preparation method described above.
[0088] It should be understood that the electrolyte includes the aforementioned organic-inorganic composite material. Therefore, all the features and advantages described above for the "organic-inorganic composite material" also apply to the "electrolyte", and will not be repeated here.
[0089] In this article, the term "electrolyte" refers to the carrier for ion transport in a lithium battery.
[0090] It should be noted that the organic-inorganic composite material described above in this application is a component present in a relatively small amount in the electrolyte.
[0091] In some optional embodiments, the amount of the organic-inorganic composite material added accounts for 1% to 4% of the total mass of the electrolyte; as an example, the amount of the organic-inorganic composite material added can be 1%, 2%, 3%, 4%, 5% of the total mass of the electrolyte, etc., or of course any value within the above range and all ranges and sub-ranges.
[0092] In some alternative embodiments, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, or ethyl acetate.
[0093] In some alternative embodiments, the electrolyte salt includes at least one of LiPF6, LiFSI, LiTFSI, LiBF4, LiClO4, or LiBOB.
[0094] In some alternative embodiments, the concentration of the electrolyte salt is 0.8-1.2 mol / L; as an example, the concentration of the electrolyte salt can be 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, etc., or of course any value within the above range and all ranges and sub-ranges.
[0095] In some optional embodiments, the organic solvent includes, but is not limited to, one or more of ethylene carbonate, propylene carbonate, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, or ethyl acetate. The organic solvent may be a mixture of two or more of the above-mentioned organic solvents, and their proportions are not particularly limited and can be appropriately selected according to actual needs, as long as the technical solution of this application can be achieved. For example, in the embodiments of this application, when the organic solvent contains two different organic solvents, they can be mixed and used in volume ratios of 1:1, 1:2, 1:3, 3:1, 2:1, 1:1.5, 1:2.5, etc.
[0096] In addition, as an improvement to the electrolyte of this application, other functional additives known in the art that can be used to improve the performance of electrolytes may be added to the electrolyte, such as one or more of film-forming agents, flame retardants, overcharge prevention additives, high voltage protectants, conductivity promoters and other functional additives, which will not be elaborated here.
[0097] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0098] Example 1 (1) Preparation of organic-inorganic composite materials S1: The hydroxyl-terminated multi-arm prepolymer is treated with the functionalizing agent to obtain a functionalized multi-arm star molecule. The specific steps are as follows: S11: A compound containing at least four hydroxyl groups (10 mmol pentaerythritol) and a lactone compound (50 mmol ε-caprolactone) were added to a reaction flask, and 0.1 mmol stannous octoate was added as a catalyst. The reaction was carried out at 110 °C for 8 hours under nitrogen protection to obtain a hydroxyl-terminated multi-arm prepolymer. S12: Add a functionalizing agent (20 mmol of 3-(isobutenoyloxy)propyltrimethoxysilane) to the above hydroxyl-terminated multi-arm prepolymer, react at 90°C for 4 hours, cool and dissolve in dichloromethane, precipitate and purify with methanol to obtain the functionalized multi-arm star molecule.
[0099] S2: The temperature-responsive molecule reacts with the functionalized multi-armed star molecule to obtain a temperature-responsive molecule-modified multi-armed star molecule. The specific steps are as follows: The above-mentioned 5 mmol functionalized multi-armed star molecule, temperature-responsive molecule (50 mmol N-isopropylacrylamide, 5 mmol acrylic acid) and 0.5 mmol azobisisobutyronitrile were added to a reaction flask, 100 mL tetrahydrofuran was added as solvent, and the reaction was carried out at 60 °C for 12 hours under nitrogen protection. After dialysis purification, the molecule was freeze-dried to obtain the temperature-responsive molecule modified multi-armed star molecule.
[0100] S3: The temperature-responsive molecule-modified multi-armed star-shaped molecule is reacted with the inorganic particles to obtain the organic-inorganic composite material. The specific steps are as follows: S31: Take 5g of Al2O3 nanoparticles (particle size 20nm) and treat them with aminosilane (10mL 3-aminopropyltriethoxysilane) to obtain aminated inorganic particles. S32: 1g of silane-treated inorganic particles and 2g of temperature-responsive molecularly modified multi-arm star molecules were added to 100mL of dichloromethane and ultrasonically dispersed at 30 kHz for 30 minutes. Then, 0.5g of N,N'-dicyclohexylcarbodiimide and 0.1g of 4-dimethylaminopyridine were added, and the mixture was reacted at room temperature for 24 hours to obtain an organic-inorganic composite material.
[0101] (2) Preparation of electrolyte The organic-inorganic composite material was added to the base electrolyte at a ratio of 2 wt%. The organic solvent of the base electrolyte was ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1. The electrolyte salt was 1 mol / L lithium hexafluorophosphate (LiPF6). The mixture was magnetically stirred for 24 hours until it was completely dissolved to obtain the electrolyte.
[0102] Example 2 The specific implementation method is the same as in Example 1, except that the lactone compound is η-heptyl lactone.
[0103] Example 3 The specific implementation method is the same as in Example 1, except that the lactone compound is δ-pentanolactone.
[0104] Example 4 The specific implementation method is the same as in Example 1, except that the lactone compound is ξ-octyl lactone.
[0105] Example 5 The specific implementation method is the same as in Example 1, except that the organic-inorganic composite material is added to the basic electrolyte at a ratio of 1 wt%.
[0106] Example 6 The specific implementation method is the same as in Example 1, except that the organic-inorganic composite material is added to the basic electrolyte at a ratio of 3wt%.
[0107] Example 7 The specific implementation method is the same as in Example 1. The difference from Example 1 is that in step S3 of the preparation of organic-inorganic composite materials, the inorganic particles are ZrO2.
[0108] Example 8 The specific implementation method is the same as in Example 1. The difference from Example 1 is that in step S3 of the preparation of organic-inorganic composite material, the inorganic particles are TiO2.
[0109] Comparative Example 1 A basic electrolyte is provided, wherein the organic solvent of the basic electrolyte is ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1, and the electrolyte salt is 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte is obtained by magnetic stirring for 24 hours until it is completely dissolved.
[0110] Comparative Example 2 A basic electrolyte is provided, the specific implementation of which is the same as in Example 1, except that the organic-inorganic composite material is added to the basic electrolyte at a ratio of 0.5 wt%.
[0111] Comparative Example 3 A basic electrolyte is provided, the specific implementation of which is the same as in Example 1, except that the organic-inorganic composite material is added to the basic electrolyte at a ratio of 5wt%.
[0112] Comparative Example 4 The specific implementation method is the same as in Example 1, except that the lactone compound is γ-butyrolactone.
[0113] Performance testing 1. Molecular testing of hydroxyl-terminated multi-arm prepolymers GPC measurement steps: Sample preparation: The multi-arm prepolymers prepared in Examples 1-4 and Comparative Example 4 were dissolved in chromatographic grade tetrahydrofuran at a concentration of 3 mg / mL, filtered through a 0.22 μm filter membrane, and tested.
[0114] Test conditions: Instrument: Agilent 1260 Infinity gel permeation chromatograph equipped with a refractive index detector (RID).
[0115] Chromatographic columns: The chromatographic system consists of one Agilent PLgel Guard column (7.5 mm × 50 mm, particle size 10 μm) and three analytical columns connected in series: an Agilent PLgel 5 μm MIXED-C column (7.5 mm × 300 mm, mixed pore size 102 Å ~ 105 Å), an Agilent PLgel 5 μm 100 Å column (7.5 mm × 300 mm), and an Agilent PLgel 5 μm 500 Å column (7.5 mm × 300 mm). Mobile phase: tetrahydrofuran, flow rate 1.0 mL / min Column temperature: 40℃ Standards: The standard used was the Agilent Narrow Distribution Polystyrene Standard Kit (catalog number PL2010-0101), which contained 9 sets of standards with different molecular weights, ranging from 580 to 255,000 g / mol, and all standards had a PDI ≤ 1.05.
[0116] Sample preparation: Accurately weigh 10.00 mg of each polystyrene standard, dissolve and dilute to volume with 10 mL of chromatographically pure tetrahydrofuran to prepare a 1.0 mg / mL standard solution. After standing at room temperature in the dark for 30 min, filter through a 0.22 μm filter membrane and put the filtrate into a GPC sample vial for testing.
[0117] Data processing: Calibration and Standard Curve: After the chromatographic system was fully equilibrated, samples were injected sequentially in ascending order of molecular weight, with an injection volume of 50 μL. Each standard sample was tested twice in parallel, and the average retention time was recorded. A retention time-lgMw calibration curve was established using a fourth-order polynomial fitting with retention time as the x-axis and lgMw as the y-axis. The curve equation is as follows: Y=10.1260 0.5280X + 0.0094X 2 4.20× 10 5 X 3 +6.80×10 8 X 4 Curve Determination R 2 =0.9998, the calibration curve is valid for 7 days. When testing the sample, the instrument automatically calculates the molecular weight and distribution parameters based on this calibration curve.
[0118] Inject the sample and obtain the GPC spectrum (vertical axis dw / d(logM), horizontal axis logM). The software automatically performs integration calculations (the integration interval covers the entire elution peak of the sample, and the baseline is determined by the flat regions before and after the peak): Mn (number-average molecular weight) = Σ(Ni×Mi) / ΣNi Mw (weight-average molecular weight) = Σ(Ni×Mi²) / Σ(Ni×Mi) PDI (molecular weight distribution) = Mw / Mn The test results are recorded in Table 1 below. The arm length is calculated according to Formula II: Formula II Marm is the arm length of the multi-arm prepolymer, in kg / mol; Mn is the number-average molecular weight of the multi-arm prepolymer, in kg / mol; and f is the number of arms of the multi-arm prepolymer.
[0119] Table 1:
[0120] As can be seen from the data in Table 1, the PDI of the obtained hydroxyl-terminated multi-arm prepolymers is in the range of 1.0 to 2.0. In particular, when the lactone compound is δ-pentanolactone, ε-caprolactone, η-heptanolactone or ξ-octanolactone, the PDI is in the range of 1.17 to 1.55. This further illustrates that the length of each arm of the hydroxyl-terminated multi-arm prepolymer provided in this application is highly consistent, which helps to form a functional layer with uniform structure and stable performance when coupled with inorganic particles in the subsequent process.
[0121] 2. Battery performance testing The electrolytes prepared in Example 1 and Comparative Example 1 were used to assemble batteries and battery performance was tested.
[0122] Battery assembly Positive electrode sheet: Positive active material (LiFePO4), conductive agent (conductive carbon black Super P) and binder (polyvinylidene fluoride, purchased from Arkema) are mixed in a mass ratio of 96:2:2 and dispersed in N-methylpyrrolidone solvent. The mixture is stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the positive current collector aluminum foil and dried at 80°C for 12 hours to form a positive active material layer. Then, it is pressed into sheets and cut into 3cm×4cm sheets to serve as positive electrode sheets.
[0123] Negative electrode sheet: Negative electrode active material (graphite), conductive agent (conductive carbon black Super P), dispersant (CMC, purchased from Noryon), and binder (SBR, purchased from Zhejiang Chuanhua Chemical) are mixed in a mass ratio of 97:0.6:1.2:1.2 and dispersed in water. The mixture is stirred evenly to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil and dried at 80℃ for 12 hours to form a negative electrode active material layer. Then, it is pressed into sheets and cut into 3.4cm×4.4cm sheets to serve as negative electrode sheets.
[0124] Separator: Ceramic separator, 10μm thick (PP base film thickness is 5μm, ceramic thickness is 2μm, PVDF adhesive thickness is 3μm), purchased from Xingyuan Material Manufacturer.
[0125] Electrolyte: The electrolytes prepared in the examples and comparative examples.
[0126] Battery: After welding the positive and negative electrode tabs together using an ultrasonic welding machine, the positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to isolate them. The battery is then placed in an outer aluminum-plastic film packaging. The electrolyte prepared above is injected into the dried battery cell. After vacuum sealing, settling, and formation processes, the battery is obtained. (The battery obtained in Example 1 is designated as Improvement Group 2#; the battery obtained in Comparative Example 1 is designated as Baseline Group 1#).
[0127] Cyclic performance: Cyclic test at 25°C at 1C rate; 1) Test temperature: 25℃±2℃, using a constant temperature chamber; 2) Two clamps, 300kgf, 0.5mm gap; 3) A battery health status check is performed every 100 cycles. The discharge capacity of the first battery health status check is recorded as C0, and the discharge capacity of the Nth battery health status check is recorded as Cn; capacity retention rate = (Cn / C0) * 100%. The test results for baseline group 1# and improved group 2# are shown in [link to test results]. Figure 1 ; Battery DCR (Direct Current Resistance) test: DCR test performed at 25℃ at 1C rate. The capacity of battery #2 in improvement group was calibrated to obtain the calibrated capacity C0. Then, a DC internal resistance test was performed on the battery, specifically including: letting the battery rest for 120 minutes, charging it to 3.65V with a constant current of 1 / 3C0, then charging it with a constant voltage until the current drops to 0.05C0, letting it rest for 30 minutes; discharging it with a constant current of 1 / 3C0 to adjust the state of charge to 90% SOC, letting it rest for 60 minutes; pulse discharging it with a constant current of 1C0 for 60 seconds, taking a sample every 0.1 seconds to record the first DC internal resistance at 90% SOC; letting it rest for 5 minutes; adjusting the state of charge to 50% SOC with a constant current of 1 / 3C0, letting it rest for 60 minutes; and pulse discharging it with a constant current of 2C0. For 60 seconds, a point is taken every 0.1 seconds to record the second DC internal resistance at 50% SOC; let it rest for 5 minutes; adjust the state of charge to 20% SOC with a constant current of 1 / 3C0, and let it rest for 60 minutes; pulse discharge with a constant current of 2C0 for 60 seconds, taking a point every 0.1 seconds to record the third DC internal resistance at 20% SOC; let it rest for 5 minutes; adjust the state of charge to 17% SOC with a constant current of 1 / 3C0, and let it rest for 60 minutes; pulse discharge with a constant current of 1C0 for 60 seconds, taking a point every 0.1 seconds to record the fourth DC internal resistance at 17% SOC; let it rest for 5 minutes; finally, discharge with a constant current of 1 / 3C0 to the termination voltage of 2.5V. The test results are shown in [see details]. Figure 2 Improvement Group 2#; The DCR test method for the batteries in the baseline group 1# is completely consistent with that of the improved group 2#. The test results are shown in [link to test results]. Figure 2 The baseline group 1#.
[0128] Rate performance: Discharge capacity was tested at different rates from 0.33C to 2C; 1) Test temperature: 25±2℃; 2) Protection voltage: 1.9V-3.7V. The discharge results of Improved Group 2# at different rates are shown below. Figure 3 The discharge of reference group 1# at different rates is shown in the figure. Figure 4 The specific data is shown in Table 2; Table 2:
[0129] pass Figures 1-4As can be seen from the data presented in Table 2, the electrolyte with the organic-inorganic composite material provided in this application significantly improves the stability of the positive electrode / electrolyte interface, and the 2C rate discharge capacity retention rate reaches more than 98%. Compared with the basic electrolyte without the addition of organic-inorganic composite material, the performance is significantly improved, and the fast charging capability of the battery is significantly enhanced.
[0130] High-temperature performance: Storage tests were conducted at 60°C. 1) Perform a battery health status check every 100 cycles. The discharge capacity of the first battery health status check is recorded as C0. 2) Perform a check on remaining capacity Cp, reversible capacity Cq, and battery health status every 30 days. Capacity retention rate = (Cp / C0) * 100%, Capacity recovery rate = (Cq / C0) * 100%; 3) Two clamps, 300kgf, 0.5mm gap; 4) Protection voltage: 1.9~3.7V.
[0131] The test results of the 60℃ storage capacity retention rate of the baseline group 1# and the improved group 2# are shown below. Figure 5 The test results of the storage capacity recovery rate at 60℃ for benchmark group 1# and improved group 2# are shown in the figure. Figure 6 ; See Table 3 for specific data.
[0132] Table 3:
[0133] Low-temperature cycling test: Cyclic testing is conducted at -20℃. 1) Perform a battery health status check every 100 cycles. The discharge capacity of the first battery health status check is recorded as C0. 2) Discharge capacity Cw after 300 cycles; Capacity retention rate = (Cw / C0)*100%. The test results of the baseline group 1# and the improved group 2# are shown in Table 4.
[0134] 3) Two clamps, 300kgf, 0.5mm gap; 4) Protection voltage: 1.9~3.7V.
[0135] Table 4
[0136] The performance test results of all embodiments and comparative assembly batteries are shown in Table 5.
[0137] Table 5
[0138] Based on the data in Tables 3 and 4, and Figure 5 , Figure 6 It can be seen that the battery with the added organic-inorganic composite electrolyte provided in this application exhibits significantly improved high and low temperature cycling performance and storage performance. After 60 days of storage at 60°C, the capacity loss decreased from 10.6% (Comparative Example 1) to 6.5% (Example 1); the 60-day storage capacity recovery rate decreased from 12% to 8%, increasing the battery's cycle life. At -20°C, the capacity retention rate after 300 cycles was 87.14%, achieving stable application of the electrolyte within a wide temperature range of -20°C to 60°C.
[0139] As shown in Table 5, the arm length, number-average molecular weight, and PDI of the hydroxyl-terminated multi-arm prepolymers in the organic-inorganic composite material provided in this application play a positive role in promoting the application of the organic-inorganic composite material in the electrolyte. Furthermore, the hybrid design of the organic-inorganic composite material provided in this application not only effectively blocks interfacial heat transfer between the electrolyte and the cathode material, but also allows for ordered rearrangement at high temperatures to form a denser interfacial protective layer. This significantly improves the stability and protective effect of the organic-inorganic composite material in high-temperature environments, ultimately achieving improved battery rate performance and fast-charging capability, as well as stable application within a wide temperature range of -20℃ to 60℃, thus achieving the invention's objective.
[0140] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0141] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the scope of the present invention to the specific details described above.
[0142] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An organic-inorganic composite material, characterized in that, It was obtained through the reaction of multi-arm star molecules modified with inorganic particles and temperature-responsive molecules; among which... The temperature-responsive molecule-modified multi-armed star molecule is obtained by reacting at least one temperature-responsive molecule with at least one functionalized multi-armed star molecule; The functionalized multi-arm star molecule comprises at least one hydroxyl-terminated multi-arm prepolymer obtained by treatment with a functionalizing agent; The structure of the hydroxyl-terminated multiarm prepolymer is shown in Formula I: Formula I, Wherein, B is the non-hydroxyl portion of a compound containing at least four hydroxyl groups, and n is 4 to 8; Ar for R is a substituted or unsubstituted C4-C7 alkyl group.
2. The organic-inorganic composite material according to claim 1, characterized in that, The hydroxyl-terminated multiarm prepolymer satisfies at least one of the following conditions: (1) The number average molecular weight of the hydroxyl-terminated multiarm prepolymer is 15~50 kg / mol; (2) The arm length of the hydroxyl-terminated multi-arm prepolymer is 6.5~13 kg / mol; (3) The PDI of the hydroxyl-terminated multiarm prepolymer is 1.0~2.
0.
3. The organic-inorganic composite material according to claim 1, characterized in that, The raw materials for preparing the hydroxyl-terminated multiarm prepolymer include the compound containing at least four hydroxyl groups and the lactone compound, and satisfy at least one of the following conditions: (1) The compound containing at least four hydroxyl groups includes polyols with a functionality of 4 to 8; (2) The compound containing at least four hydroxyl groups includes at least one of pentaerythritol, dipentaerythritol, inositol or sorbitol; (3) The lactone compound includes at least one of δ-valerolactone, ε-caprolactone, η-heptylactone or ξ-octylactone.
4. The organic-inorganic composite material according to claim 1, characterized in that, The functionalized reagent contains an olefinic unsaturated component that can polymerize with temperature-responsive molecules; And / or, the functionalizing agent includes at least one of 3-(isobutenoyloxy)propyltrimethoxysilane or vinyltrimethoxysilane.
5. The organic-inorganic composite material according to claim 1, characterized in that, The temperature-responsive molecule comprises at least one temperature-responsive monomer and at least one unsaturated carboxylic acid, and satisfies at least one of the following conditions: (1) The temperature-responsive monomer includes at least one of N-isopropylacrylamide, N-vinylcaprolactam, N,N-dimethylaminoethyl methacrylate, N,N-diethylacrylamide, 2-hydroxyethyl acrylate, N-isopropylmaleimide or 2-isopropenyl-2-oxazoline; (2) The unsaturated carboxylic acid includes at least one of acrylic acid, methacrylic acid, itaconic acid, maleic acid or fumaric acid.
6. The organic-inorganic composite material according to claim 1, characterized in that, The inorganic particles satisfy at least one of the following conditions: (1) The inorganic particles include at least one of Al2O3, ZrO2, TiO2 or SiO2; (2) The inorganic particles are obtained by treatment with aminosilane; the aminosilane includes at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane or N-octadecyl-aminopropyltrimethoxysilane. (3) The particle size of the inorganic particles is 10nm~50nm.
7. A method for preparing an organic-inorganic composite material according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1: Treat the hydroxyl-terminated multi-arm prepolymer with the functionalizing agent to obtain a functionalized multi-arm star molecule; S2: The temperature-responsive molecule reacts with the functionalized multi-armed star molecule to obtain a temperature-responsive molecule-modified multi-armed star molecule; S3: React the temperature-responsive molecule-modified multi-armed star-shaped molecule with the inorganic particles to obtain the organic-inorganic composite material.
8. The preparation method according to claim 7, characterized in that, The weight ratio of the inorganic particles and the temperature-responsive molecule-modified multi-armed star-shaped molecules in S3 is 1:(1~5).
9. An electrolyte, characterized in that, It includes electrolyte salts, organic solvents, and organic-inorganic composite materials as described in any one of claims 1 to 6, or organic-inorganic composite materials prepared by the preparation method described in any one of claims 7 to 8.
10. The electrolyte according to claim 9, characterized in that, At least one of the following conditions must be met: (1) The amount of the organic-inorganic composite material added accounts for 1% to 4% of the total mass of the electrolyte; (2) The organic solvent includes at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate or ethyl acetate; (3) The electrolyte salt includes at least one of LiPF6, LiFSI, LiTFSI, LiBF4, LiClO4, and LiBOB; (4) The concentration of the electrolyte salt is 0.8-1.2 mol / L.